The History of the Millennium of Poland from the Perspective of Radio Free Europe’s Broadcasts, 1960-1966 - Młynarczyk-Tomczyk, Anita (Historiografías, 2022)
A significant element of activity of Radio Free Europe (RFE) were broadcasts of educational character, reminding, especially young generation behind the “iron curtain”, of Polish political history and the development of Polish culture. During the celebration of “Polish Millennium” (1960-1966), the editorial board of RFE played an important role in popularizing a thousand-year-old history of the nation, Christianity and Polish country. Many of the lectures addressed to the society of communist Poland were of up-to-date significance. In that way, the RFE editors opened the “gate to the West”, closed by the communist authorities. Many events from Poland’s 1000-year history were interpreted in an anti-communist spirit, exposing the significant role of the Catholic Church.